2021
DOI: 10.1177/03000605211036832
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of inhibitory costimulatory molecules and correlations with levels of innate immune cytokines in patients with pulmonary tuberculosis

Abstract: Objective To analyze serum levels of inhibitory costimulatory molecules and their correlations with innate immune cytokine levels in patients with pulmonary tuberculosis (PTB). Methods Data for 280 PTB patients and 280 healthy individuals were collected. Serum levels of immune molecules were measured using ELISA. Univariate, multivariate, subgroup, matrix correlation, and receiver operating characteristic curve analyses were performed. Results Host, environment, lifestyle, clinical features, and medical histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The role of this cytokine in HIV-1 infection and TB has already been described ( Xuan et al., 2014 ; Wu et al., 2018 ), which shows potential therapeutic effects on established MTB infections, which might represent a novel therapy for PTB ( Piñeros et al., 2017 ). Zhao et al., 2021 showed that the plasma IL-33 levels were significantly higher in individuals with PTB than in healthy individuals ( Zhao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of this cytokine in HIV-1 infection and TB has already been described ( Xuan et al., 2014 ; Wu et al., 2018 ), which shows potential therapeutic effects on established MTB infections, which might represent a novel therapy for PTB ( Piñeros et al., 2017 ). Zhao et al., 2021 showed that the plasma IL-33 levels were significantly higher in individuals with PTB than in healthy individuals ( Zhao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 33 articles were included, including three in Chinese [21–23] and 30 in English. [9,11,12,14,24–49] The literature retrieval process is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 33 articles included, [9,11,12,14,21–49] 51 studies were included, comprising 2379 patients with TB and 1391 healthy adults, including 2113 patients with pulmonary TB, 266 with extrapulmonary TB, 25 with multidrug-resistant TB, 2000 with active TB, and 379 with latent TB. Tables 1 and 2 provide basic information about the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations